PELAKSANAAN PENYALURAN BANTUAN PANGAN NON TUNAI (BPNT) BAGI PENERIMA MANFAAT DALAM KESEJAHTERAAN KELUARGA MISKIN DI KELURAHAN PONDOK BAHAR KECAMATAN KARANG TENGAH KOTA TANGERANG - Zihar Narvaes1 , Giraf; Inneka Widyawati, Tito (Jurnal MoZaiK, 2023)
In carrying out the mandate of the 1945 Constitution of the Unitary State of the Republic of Indonesia, the State is responsible for what is experienced by its people. Realizing a just and prosperous society and remembering that the poverty rate in Indonesia is still relatively high. Through the Non-Cash Assistance Program (PBNT) with the aim of reducing the expenditure burden on Beneficiary Families (KPM) in Pondok Bahar Village, Karang Tengah District, Tangerang City. Using qualitative descriptive research methods, research is used to describe events and phenomena that occur in the field. Data collection was carried out through interviews, observation and documentation. This research shows that (1) General Description of the Non-Cash Food Assistance Program, there are four processes. Namely, Registration or Opening an Account, Education and Socialization, Distribution, Purchase of Goods. (2) The implementation of the Non-Cash Food Assistance Program in Pondok Bahar Village, Karang Tengah District is considered good by using E-warong as a place to purchase food. (3) The Non-Cash Food Assistance Program has supporting factors, namely a government that is responsive to obstacles that occur to Beneficiary Families. Keyword: Non-Cash Food Assistance, Welfare, Poor Families